Influence of batch-specific biochemical egg characteristics on embryogenesis and hatching success in farmed pikeperch. (4th December 2017) - Schaefer, F. J.; Overton, J. L.; Krüger, A.; Kloas, W.; Wuertz, S.
Abstract : Low and variable egg quality remains a major issue in aquaculture impeding a reliable and continuous supply of larvae, particularly in emerging species, such as pikeperch, Sander lucioperca . We assessed the influence of batch-specific egg parameters (fatty acid (FA) profiles, cortisol content) on embryo life-stages until hatching (survival at 2, 24, 48, 72 h post fertilization (hpf), hatching rate) in an integrated study under commercial hatchery conditions (44 egg batches). Embryo mortality was elevated until 48 hpf (average 9.8% mortality between 2 and 48 hpf). Embryos surviving until 48 hpf were very likely (98.5%) to hatch successfully. The inherent egg FA composition was variable in-between batches. Total FA content ranged form 66.1 to 171.7 µg/mg (dry matter) total FA. Whereas specific FA, 18 : 0 and 20 : 5(n-3) (eicosapentaenoic acid) of the polar fraction and the ratio of 22 : 6(n-3) (docosahexaenoic acid) to 20 : 5(n-3) within the neutral fraction, were significantly correlated with early embryo development, contents of the respective FA did not differ between high (>90% hatching rate), mid (70% to 90% hatching rate) and low (<70% hatching rate) quality egg batches. Late embryo development and hatching were relatively independent of the FA profiles highlighting stage-dependent influences especially during early embryogenesis. Cortisol levels ranged from 22.7 to 293.2 ng/ml and did not directly explain for mortalities. However, high cortisol was associated with a lower content of specific FA, in particular highly unsaturated FA. These results demonstrate the magnitude of inter-individual differences in the batch-specific biochemical egg composition under stable hatchery conditions and suggest a stress-mediated lack of essential FA, which in turn affects early embryo survival. Surprisingly, embryos are able to cope well with a broad range of inherent egg parameters, which limits their predictive potential for egg quality in general. Still, specific FA profiles of high quality egg batches have potential for formulating species-specific broodstock diets and improving reproductive management in pikeperch.